Quantifying the resilience of European farms using FADN. (13th October 2021) - Slijper, Thomas; de Mey, Yann; Poortvliet, P Marijn; Meuwissen, Miranda P M
Abstract: Agricultural policymakers call for the operationalisation of farm resilience as a dynamic concept. Therefore, we quantify farm resilience along the dimensions of robustness, adaptation and transformation. Using the rich Farm Accountancy Data Network panel data set, we explore which farm(er) characteristics affect resilience. We employ a control function approach to address the presence of endogeneity in correlated random effects (fractional) probit models. In general, we find that decoupled payments negatively affect robustness, while rural development payments have a positive effect on robustness. Both decoupled and rural development payments have no effect on adaptation and transformation in most European regions.